2008
DOI: 10.1063/1.2888744
|View full text |Cite
|
Sign up to set email alerts
|

Variability of electronics and spintronics nanoscale devices

Abstract: We address the problem of how the quantum ͑and the temperature͒ fluctuations will affect the magnetoelectronic circuits' operation, and if there are any advantages, or possibly drawbacks, in the switching from the charge for uncorrelated electronics to the spin for spintronics. Within the framework of "minimal" ferromagnetic Hamiltonian, we consider the fluctuations in the total number of the electrons on the gate, the total spin, and the spin vector projection on the easy axis. It is expected that spintronics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Another aspect of practicality lies in variability benefits between spin and electron charge, in particular toward thermal and quantum fluctuations. It has recently been shown that spintronic devices can improve variability compared with today's charge-based devices as variability of spintronic devices has been shown to be limited only by thermal fluctuations, and not by quantum fluctuations as for electronic devices [60]. However, a major drawback in a practical spin-based device is the lack of any demonstrated spin "gain" device that is required for spin circuit fan-out.…”
Section: Discussionmentioning
confidence: 98%
“…Another aspect of practicality lies in variability benefits between spin and electron charge, in particular toward thermal and quantum fluctuations. It has recently been shown that spintronic devices can improve variability compared with today's charge-based devices as variability of spintronic devices has been shown to be limited only by thermal fluctuations, and not by quantum fluctuations as for electronic devices [60]. However, a major drawback in a practical spin-based device is the lack of any demonstrated spin "gain" device that is required for spin circuit fan-out.…”
Section: Discussionmentioning
confidence: 98%
“…There are different sources of variability due to thermal and quantum fluctuations, resulted from fluctuations of the number of electrons, for example, and process control such as pattern size and dopant variations in semiconductor FET. We will, however, in this paper look at the fundamental of quantum fluctuations [3].…”
Section: Variability Of Electronics and Spintronicsmentioning
confidence: 99%
“…In such a regime near the thermal limit [Meindl et al 2001]-when switching energy barely exceeds that of thermal noise-the law of large numbers ceases to hold, and fluctuations will play a prominent role [Ovchinnikov and Wang 2008]. Since noise and fluctuations compromise the reliability of VLSI systems, various strategies have been devised to counter their effects.…”
Section: Introductionmentioning
confidence: 99%